2014
DOI: 10.1016/j.bjoms.2014.07.053
|View full text |Cite
|
Sign up to set email alerts
|

The Validity of 3dMD Vultus in Predicting Soft Tissue Morphology Following Orthognathic Surgery

Abstract: Objectives:To determine the validity of 3dMD Vultus in predicting soft tissue morphology following orthognathic surgery. Methods:Thirteen patients with a skeletal discrepancy that required surgical correction limited to a Le Fort I surgical advancement osteotomy were included within the study. These patients had previously undergone a CBCT scan immediately before surgery (T1) and 6 months after surgery (T2).To permit validation, hard and soft tissues were linked for each time point and the hard tissues superim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 204 publications
(186 reference statements)
0
3
0
1
Order By: Relevance
“…However, the application of 3dMD for postoperative facial assessment of edentulous jaw patients is less reported nowadays, making this study is highly innovative. [18][19][20][21][22] Additionally, 3D Facial Scanning technology can effectively validate the facial transformation before and after dental implant restoration in toothless patients. This technology may aid surgeons in planning surgery more precisely and enhance communication between physicians and patient.…”
Section: Discussionmentioning
confidence: 99%
“…However, the application of 3dMD for postoperative facial assessment of edentulous jaw patients is less reported nowadays, making this study is highly innovative. [18][19][20][21][22] Additionally, 3D Facial Scanning technology can effectively validate the facial transformation before and after dental implant restoration in toothless patients. This technology may aid surgeons in planning surgery more precisely and enhance communication between physicians and patient.…”
Section: Discussionmentioning
confidence: 99%
“…[ 60 , 61 ] After evaluating the changes of facial soft-tissue before and 6 months after the surgery in 13 patients through CT and stereophotogrammetry, Ullah et al found that it is clinically acceptable to predict facial soft-tissue changes through 3D optical measurement. [ 62 ] Using 3D optical devices to assist the formulation of surgical plan and the evaluation of curative effect cleft lip and palate is another application in stomatology. By comparing 3D facial morphology between children with cleft lip and palate and healthy children using laser-based scanning, Djordjevic et al evaluated the effect of cleft lip and palate repair in an objective way.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that software programs can produce clinically acceptable soft tissue predictions in craniofacial reconstruction, head and neck reconstruction, and orthognathic patients. 20,21 This is particularly useful in understanding facial symmetry, but the accuracy and reproducibility has its inherent challenges with hair covering the skull. It has also been reported that operator and recalibration errors are negligible as seen across other similar 3D imaging systems.…”
Section: Discussionmentioning
confidence: 99%